2007
DOI: 10.1542/peds.2006-1746
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-Month Effectiveness of a Parent-led, Family-Focused Weight-Management Program for Prepubertal Children: A Randomized, Controlled Trial

Abstract: Parenting-skills training combined with promoting a healthy family lifestyle may be an effective approach to weight management in prepubertal children, particularly boys. Future studies should be powered to allow gender subanalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
220
2
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(245 citation statements)
references
References 29 publications
17
220
2
6
Order By: Relevance
“…The interventions to treat obesity could broadly be categorized into three groups: interventions aimed at modifying behaviour, diet and/or physical activity delivered to groups of children and/or parents 24,26,29,31,33 or delivered to individual families; 25,27,30 and technology-based interventions used in the home or community aimed at promoting physical activity or reducing sedentary activities. 28,32 For the group-based interventions, planned contact time with professionals ranged from 10 (ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interventions to treat obesity could broadly be categorized into three groups: interventions aimed at modifying behaviour, diet and/or physical activity delivered to groups of children and/or parents 24,26,29,31,33 or delivered to individual families; 25,27,30 and technology-based interventions used in the home or community aimed at promoting physical activity or reducing sedentary activities. 28,32 For the group-based interventions, planned contact time with professionals ranged from 10 (ref.…”
Section: Resultsmentioning
confidence: 99%
“…28,32 For the group-based interventions, planned contact time with professionals ranged from 10 (ref. 24) to 128 (ref. 29) hours delivered over periods ranging from 5 --12 months to groups of between 7 and 14 children and/or families.…”
Section: Resultsmentioning
confidence: 99%
“…4 Typically, obesity interventions in children include treatment-seeking families or recruit via advertisement or referrals. [11][12][13][14][15] The widespread inability of both parents 16 and health professionals 17 to correctly identify children as overweight limits intervention to the very overweight. This seems sensible given that obese children have greater health risks and are more likely to be obese adults than mildly overweight children.…”
Section: What This Study Addsmentioning
confidence: 99%
“…This approach emphasizes the importance of parental modeling and authority over the home environment (Golan & Weizman, 2001), as well as engaging the parents as agents of change (Apter, Fainaru, Golan, & Weizman, 1998). Parent-only approaches have been tested in 14 trials included in this review (Apter et al, 1998;Bean, Wilson, Thornton, Kelly, & Mazzeo, 2012;Collins et al, 2011;Golan & Crow, 2004;Golan, Kaufman, & Shahar, 2006;Golley, Magarey, Baur, Steinbeck, & Daniels, 2007;Janicke et al, 2008;Jansen, Mulkens, & Jansen, 2011;Magarey et al, 2011;Mazzeo et al, 2014;Moens & Braet, 2012;Morgan et al, 2014;Munsch et al, 2008;Okely et al, 2010;Shelton et al, 2007). In two trials, Golan and colleagues found FBT with parents as the agents of change more effective than FBT with children as the agents of change for both children (Golan et al, 2006) and adolescents (Apter et al, 1998), with the parentfocused treatment remaining superior at 7-year follow-up (Golan & Crow, 2004), although it should be noted that this study was conducted within a different region and culture (Israel with two-parent families).…”
Section: Parent-only Behavioral Treatmentmentioning
confidence: 99%